2016
DOI: 10.3109/14756366.2016.1170013
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the mechanism of inhibition of tryptophan 2,3-dioxygenase by isatin derivatives

Abstract: Tryptophan 2,3-dioxygenase (TDO) is a cytosolic protein with a proven immunomodulatory function that promotes tumoral immune resistance and proliferation. Despite the interest in TDO as a therapeutic target in cancer treatment, the number of biologically useful inhibitors is limited. Herein, we report isatin derivatives as a new class of TDO inhibitors. Through structureactivity relationships and molecular docking studies, we optimized the inhibition potency of isatin derivatives by 4130-fold and elucidated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…Several research groups had successfully taken advantage of these hydrophobic interactions in the optimization of the IDO1 inhibition efficacies. 4,12,13 21 This also endorses the importance of C3-substituted oxindole moieties in designing inhibitors for these enzymes. The inhibition efficacies of these oxindole derivatives were determined by a spectrophotometric method.…”
Section: Inhibitory Activities Of the Oxindole Derivatives Against Pumentioning
confidence: 75%
See 1 more Smart Citation
“…Several research groups had successfully taken advantage of these hydrophobic interactions in the optimization of the IDO1 inhibition efficacies. 4,12,13 21 This also endorses the importance of C3-substituted oxindole moieties in designing inhibitors for these enzymes. The inhibition efficacies of these oxindole derivatives were determined by a spectrophotometric method.…”
Section: Inhibitory Activities Of the Oxindole Derivatives Against Pumentioning
confidence: 75%
“…Brassinin, tryptamine, carboline, keto-indoles, indol-2-yl ethanones, 1-methyl-tryptophan-tirapazamine, isatin and other indole derivatives also showed poor to moderate IDO1 inhibitory activities. [16][17][18][19][20][21][22] Comprehensive mechanistic studies of IDO1 induced L-Trp catabolism revealed that the addition of ferrous heme-iron coordinated molecular oxygen to the C2-C3 double bond of the pyrrole ring is the prerequisite for the IDO1 supported oxidation of L-Trp. These studies also proposed the formation of an epoxide intermediate state during the transformation of L-Trp to N-formylkynurenine by the IDO1 enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…A library of 12 compounds was prepared in order to study the versatility of the method which appears to be applicable to a range of isatin starting materials in which the 3-oxo group is active for aldol reactions. Furthermore, we acquired different spectroscopic analyses such as 15 N-MASNMR, 15 N-NMR and SXRD to confirm the structure of the products. To the best our knowledge, no 15 N-MASNMR spectra on 3-hydroxypyrazole scaffolds had previously been performed.…”
Section: Discussionmentioning
confidence: 99%
“…The 3-hydroxy-2-oxindole moiety is another related and widely represented motif present in several natural products (9,10,12) [10][11][12][13][14]. This scaffold has recently been employed in several areas of pharmacology (examples in Figure 2), and it has been described in the context of anti-cancer (tryptophan 2,3-dioxygenase inhibitor, 6) [15], anticonvulsant (8) [16], cytotoxic (11) [17] and growth hormone releasing agents (i.e., SM-130686, 7) [18,19]. Several methodologies for the generation of oxindole systems have been reported with one of these employing isatin [20].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, a screening of 2,800 compounds from the library of the National Cancer Institute (USA) identified seven compounds inhibiting TDO, among them six quinones such as β-lapachone, taxifolin, nanaomycin A, and mitomycin C [130]. Later, the same group described derivatives of the naturally ocurring quinone isatin for TDO and IDO1 inhibition [131]. In these works, only enzymatic assay results were reported, and no additional tests were carried out.…”
Section: Quinonesmentioning
confidence: 99%